Król węgierski Andrzej II na tronie w Cesarstwie Łacińskim? Bałkański wątek Piątek Krucjaty - Pentek, Zdzisław (Balcanica Posnaniensia Acta et studia, 2018)
The article focuses on the participation of the Hungarian King Andrew II in the Fifth Crusade in 1217. The author rejects the speculations (B. Hóman, S. Runciman, F. Van Tricht et al.) that the reason of the king’s decision was ascending the throne of the Latin Empire after the death of the emperor Henry in 1216. Due to the lack of evidence in sources for these speculations, the author claims that the reasons for which Andrew II took part in the Fifth Crusade were rather prestigious, devotional and ambition oriented.